A DFT Study of Tungsten–Methylidene Formation on a W/ZSM‐5 Zeolite: The Metathesis Active Site. Issue 15 (25th August 2015) - Maihom, Thana; Probst, Michael; Limtrakul, Jumras
Abstract Tungsten–methylidene formation from ethene on either the WIV, WV, or WVI active sites of a W/ZSM‐5 zeolite is investigated by using the M06‐L functional. The reaction is assumed to proceed in two steps; the first step is the [2+2] cycloaddition between ethene and the W−O active site to form an oxametallacycle intermediate. The intermediate is then decomposed to produce the W–methylidene active site from the metathesis reaction. The overall activation barrier of the reaction on WVI (27.3 kcal mol−1) is considerably lower than the ones for WIV and WV (69.4 and 37.1 kcal mol−1, respectively). Moreover, the reaction involving the WVI site also stabilizes intermediates and products to a larger extent than the ones on the WIV and WV sites. As a result, we have demonstrated that the reaction of the W–methylidene metathesis active site is both kinetically and thermodynamically favored to occur on the WVI active site of the zeolite.